6th Annual Conference of the Neuropathology Society of India (NPSICON) - Meeting Abstracts, February 23–25, 2023 - Neuropathology Society of India (Free Neuropathology, 2023)
The 6th Annual conference of the Neuropathology Society of India, (NPSICON 2023) was held in a virtual mode, from 23rd to 25th February 2023, hosted by the Division of Neuropathology, Department of Pathology, Christian Medical College Vellore. Dr Geeta Chacko was the organizing Chairperson. The pre-conference workshop was on Fluorescence in situ hybridization with nearly 90 registrants. The workshop was conducted by NIMHANS Bangalore with Dr Shilpa Rao, Dr Vaishali Suri, Dr Vani Santosh and Dr Geeta Chacko as resource persons. There were 253 National registrants and 7 International registrations. The conference had participation from reputed national (34) and international (8) faculty and covered a wide range of topics in both neoplastic and non-neoplastic Neuropathology including sessions on perinatal pathology, epilepsy, neuromuscular pathology and several sessions in Neurooncology. There were five symposiums with several sessions of cases-based discussion. The first Prof Ashru K Banerjee oration was delivered by Dr Kenneth Aldape, from NIH Bethesda on: "Practical Aspects of Methylation-Based Diagnostics in Central Nervous System Tumors”. The first Prof SK Shankar oration was delivered by Dr Avindra Nath, NIH Bethesda on "Neuropathology of two pandemics: AIDS and COVID". The Presidential oration was delivered by Dr Chitra Sarkar. The key note speakers included Dr Monika Hofer, Dr David Capper, Dr Takashi Komori and Dr Maysa Husseini. There were 28 papers for oral presentation and 38 posters. A highlight of the conference was a lively Quiz competition, which was held as the penultimate session. Despite being a virtual conference, there was active participation from all the delegates and the conference was very well received.